Islamic Jurisprudential Approaches to Pesantren Financial Reporting: Constructing a Framework for Legalized Accounting Practices - Habibi, M. Luthfillah; Mahsun, Moch; Asnawi, Nur; Putra, Yuniarti Hidayah Suyoso; Arifin, Sirajul (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
This paper examines the epistemic gap between contemporary accounting methods and Islamic jurisprudence (fiqh) in the financial reporting of Pesantren, or Islamic boarding schools that operate as nonprofit organizations. Modern standards, such as IFRS, place a strong emphasis on technical compliance and objectivity. However, they frequently overlook the moral and spiritual principles—such as fairness, transparency, and trust—that are fundamental to Islamic responsibility. Fiqh, on the other hand, provides robust normative guidance but lacks the technical tools necessary for consistent reporting and implementation. By proposing an integrative model for financial reporting that balances Shariah-based ethics with modern accounting practices, this study aims to bridge this gap. This study identifies thematic trends, research gaps, and emerging frameworks in Islamic accounting by analyzing peer-reviewed papers and scholarly outputs from international academic databases using a Systematic Literature Review (SLR) approach, aided by the bibliometrix R-tool software. The results indicate that, within the context of Islamic educational institutions, there is no operational model that integrates IFRS and AAOIFI criteria. The Islamic Value-Based Accounting System (IVBAS), which emphasizes both legal compliance and spiritual responsibility, is the study's recommendation. This concept has important implications for Islamic economics and nonprofit administration. It provides Pesantren with a fresh approach to establishing Shariah-compliant and transparent reporting procedures, while boosting their credibility and stakeholder trust